LANGKAH POLYA UNTUK IDENTIFIKASI TINGKAT BERPIKIR PADA SISWA KELAS 10 IPA UNTUK MATA PELAJARAN PEMROGRAMAN WEB - ARDYMULYA ISWARDANI; NUGROHO ARIF SUDIBYO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Student thinking level influences student achievement. Measurement of students 'level of thinking with polya is expected to gain knowledge of students' ability to solve problems. Respondent data collection is done by purposive sampling and snowball which is then analyzed by polya results of the implementation of polya steps indicate the achievements of each student. The results of this study concluded that the 10th grade science students had reached the fourth stage of the 4 polya steps. However, training is needed to increase flight hours.